1992
DOI: 10.1164/ajrccm/146.6.1434
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Envelope Protein (gp120) Inhibits the Activity of Human Bronchoalveolar Macrophages againstCryptococcus neoformans

Abstract: Cryptococcus neoformans infections are a major cause of morbidity and mortality for HIV-infected persons. Containment of the initial respiratory inoculation to the lung appears defective in patients with AIDS despite the low burden of HIV in bronchoalveolar macrophages. We have studied the fungistatic activity of human bronchoalveolar macrophages (BAM) cultured with an encapsulated strain of C. neoformans in the presence of pooled human serum. We observed 51.6% fungistasis after 24 h of culture. Fungistasis wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 7 publications
2
22
0
Order By: Relevance
“…Likewise, Shiratsuchi et al (29) found that culture of human monocytes with gp120 for 2 d inhibited the phagocytosis of M. avium, and enhanced intracellular replication. Although the exact mechanism(s) is unknown, both reports demonstrated that the effects of gp120 were mediated, in part, through binding of gp120 to M CD4 (28,29). In agreement with the present study, the latter group also found that pretreatment with p24 did not affect monocyte interactions with M. avium.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Likewise, Shiratsuchi et al (29) found that culture of human monocytes with gp120 for 2 d inhibited the phagocytosis of M. avium, and enhanced intracellular replication. Although the exact mechanism(s) is unknown, both reports demonstrated that the effects of gp120 were mediated, in part, through binding of gp120 to M CD4 (28,29). In agreement with the present study, the latter group also found that pretreatment with p24 did not affect monocyte interactions with M. avium.…”
Section: Discussionsupporting
confidence: 92%
“…Wagner et al (28) reported that culture of human alveolar M with rgp120 for 60 min decreased M fungistatic activity against C. neoformans, and decreased the ingestion of, but not the attachment of C. neoformans yeasts. Likewise, Shiratsuchi et al (29) found that culture of human monocytes with gp120 for 2 d inhibited the phagocytosis of M. avium, and enhanced intracellular replication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wagner era/. [14] found that gpl 20 pulsing of macrophages inhibited the uptake of Cryptococcus neoformans. Recent data by Wahl et al [19] has shown that gpl20 triggers the copious release of PGF.2 from macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence that both T cell and APC function can be compromised in uninfected cells of HIV ϩ patients (13)(14)(15)(16)(17)(18)(19). HIV-1-associated alteration of APC function has downstream consequences for the generation of adaptive immune responses.…”
mentioning
confidence: 99%